Sheep welfare assessment of meat farms from Spain in different breeds and production systems - Parés, Ricard; Llonch, Pol; Manteca, Xavier; Such, Xavier (Frontiers in Animal Science, 2023)
Sheep production systems are diverse in Europe, and welfare assessment should consider this diversity, including differences in breed type, climatic conditions, and time of the year. The aim of this study was to evaluate welfare in 100 commercial sheep farms in Spain, and therefore in Mediterranean conditions, using a list of 24 indicators, comprising three for good feeding, five for housing, 11 for health, and five for appropriate behavior. The list includes indicators from the AWIN protocol and other suggested indicators. Level of intensification was the main parameter that affected the welfare outcomes of feeding and health, but seasonality and flock size also affected some of the outcomes. Novel indicators included in the list (sternum evaluation, crowding behavior, subcutaneous abscesses, external parasitism, aggressive behaviors, wool pulling, ear posture, and reaction during restraint) were useful to evaluate welfare in Spanish farming conditions, but further studies should be performed to validate these indicators.